Characteristics of Kluwek (Pangium edule) Shell Charcoal Briquettes Activated with NaOH - Dwiyanti, Putri; Hendriyanto Cahyonugroho, Okik (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
Indonesia, as one of the countries with a high population, continues to face significant challenges in energy conservation. The development of alternative fuel sources is urgently required to address energy shortages, such as biocharcoal briquettes derived from biomass. Kluwek shells (Pangium edule) have potential as briquette material due to their high cellulose content, reaching 70.52%. This study aimed to evaluate the characteristics of briquettes, including moisture content, ash content, calorific value, combustion rate, and compressive strength, in accordance with the SNI 01-6235-2000 quality standards. The experimental variations included adhesive concentrations of 10%, 15%, and 20%, and mesh sizes of 30, 60, and 90. Overall, the results met the required standards. The optimal briquette characteristics were obtained from 10% NaOH-activated kluwek shell briquettes with 10% adhesive and a 30 mesh size, resulting in a moisture content of 1.65%, ash content of 3.30%, calorific value of 6191.17 Cal/g, and combustion rate of 1.13 g/min.